(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
Population structure and morphological variability of halophilic species Gypsophila paulii Klokov, G. perfoliata L. and G. scorzonerifolia Ser. have been investigated in industrial ecotopes in the south-east of Ukraine and in the region "Prydniprovje". The adaptation processes running in the populations results in predominance of young individuals in the age spectrum and in low correlation and low average variability of morphological characters. In the organism level, the investigated species distinguish by their phenotypic plasticities expressed in compensatory development of vegetative and generative organs. This is shown by absolute values of the features and also by calculated vitality classes of populations and coefficients of divergence and variation.